(untitled) (Applied Biological Research, 2025)
Sheep play a vital role in supporting rural livelihoods, particularly in arid, semi-arid, and marginal farming regions where crop and dairy production are less viable. The present study evaluated the effect of Moringa oleifera leaf meal–based diets on the blood biochemical profile of Deccani sheep reared under intensive and semi-intensive management systems. A total of thirty-six growing lambs weighing 14–18 kg were randomly allotted to three dietary treatments: T₁ (control), T₂ (75% groundnut cake + 25% Moringa leaf meal), and T₃ (50% groundnut cake + 50% Moringa leaf meal), with six lambs per group under each rearing system. The feeding trial was conducted for 90 days. Hematological and biochemical parameters were analyzed using Student’s t-test. No significant differences (P < 0.01) were observed in hematological parameters among dietary treatments in either management system. Hemoglobin concentrations ranged from 9.83 to 11.25 g dL⁻¹ across treatments, while packed cell volume values were higher in T₂ compared to T₁ and T₃. Total protein levels were significantly higher (P < 0.01) in T₃ under both rearing systems. Blood glucose levels showed a non-significant decrease in T₂ compared to T₁ and T₃. Serum glutamic oxaloacetic transaminase and serum glutamic pyruvic transaminase values remained within normal physiological limits. Overall, improved blood biomolecule profiles indicated that inclusion of 25% Moringa oleifera leaf meal under intensive rearing conditions was superior to semi-intensive management.